2019
DOI: 10.1093/mnras/stz2190
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for weak magnetic fields in Herbig Ae/Be stars

Abstract: In recent years Herbig Ae/Be stars receive considerable attention as their disks are believed to be the sites of on-going planet formation. Confirming the presence of magnetic fields in these stars is critical for understanding the transport of angular momentum during the protostellar phase. Furthermore, magnetic fields set the conditions for strongly anisotropic accretion. In this study we present the results of our recent observing campaigns of a sample of Herbig Ae/Be stars aimed at measurements of their ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Nonetheless, other measurements of the same star suggested that this could indeed be one of the HAeBes with the strongest magnetic field of several kG (see [96] and references therein), which combined with uncertainties in stellar parameters and accretion rates could be potentially consistent with the minimum magnetic field necessary to drive MA. Finally, HD 190073 is a massive HBe star and the most recent measurements in Järvinen et al (2019) [91] confirm that its magnetic field is below ∼100 G, a factor >6 smaller than the value of B min estimated here and ruling out MA as the driving mechanism for this source.…”
Section: Is Magnetospheric Accretion Plausible For Herbig Ae/be Stars?supporting
confidence: 46%
See 1 more Smart Citation
“…Nonetheless, other measurements of the same star suggested that this could indeed be one of the HAeBes with the strongest magnetic field of several kG (see [96] and references therein), which combined with uncertainties in stellar parameters and accretion rates could be potentially consistent with the minimum magnetic field necessary to drive MA. Finally, HD 190073 is a massive HBe star and the most recent measurements in Järvinen et al (2019) [91] confirm that its magnetic field is below ∼100 G, a factor >6 smaller than the value of B min estimated here and ruling out MA as the driving mechanism for this source.…”
Section: Is Magnetospheric Accretion Plausible For Herbig Ae/be Stars?supporting
confidence: 46%
“…Those strong magnetic fields are enough to sustain MA in CTTs (e.g., [20][21][22]). On the opposite, the vast majority of HAeBes show magnetic fields ≤ hundreds of G or below detection limits, as inferred from wide samples including dozens of sources (e.g., [86][87][88][89][90][91]). The contrast between both previous results is probably behind the strongest arguments against MA working in HAeBes, and it certainly motivates the question on whether this scenario is plausible for the HAeBe regime or not (see e.g., the corresponding discussions in [63,72,81,88,92]).…”
Section: Is Magnetospheric Accretion Plausible For Herbig Ae/be Stars?mentioning
confidence: 99%
“…Stellar magnetic field measurements in pre-mainsequence stars do support a strong stellar mass dependence in the strength and evolution of magnetic fields, with weaker fields below ≈ 200 G in Herbig Ae/Be stars compared to kG in T Tauri stars (e.g. Alecian et al 2013;Villebrun et al 2019;Järvinen et al 2019). In a scenario where CO traces an inner disk wind that is MHD in nature, the internal stellar structure and duration of magnetic fields could be related to the T eff dependence of line shapes, where solar-mass, convective stars typically have triangular lines tracing an inner MHD wind supported by their stronger magnetic field, while (older) Herbig Ae/Be stars with their radiative structure do not support inner MHD winds and typically have Keplerian lines tracing the disk only.…”
Section: Why a T Eff Dependence For Line Shapes?mentioning
confidence: 99%
“…We consider field strengths B * ≈ 100 -300 G as have been reported for some HAeBe stars (e.g. Hubrig et al 2004Hubrig et al , 2013Bagnulo et al 2015;Järvinen et al 2019). Taking Ṁacc ∼ 10 −8 M ⊙ yr −1 and B * ≈ 100 G gives r i ≈ 1.3 R * , v s ≈ v f f = 341 km s −1 (ignoring centrifugal forces), T s = 1.6 MK, kT s = 0.14 keV, and log L acc = 32.6 ergs s −1 .…”
Section: Hd 100546 X-ray Emission Processesmentioning
confidence: 99%